Survey of Long-Term Experiences of Sperm Cryopreservation in Oncological and Non-Oncological Patients: Usage and Reproductive Outcomes of a Large Monocentric Cohort - Lackamp, Nadine; Wilkemeyer, Ina; Jelas, Ivan; Keller, Ulrich; Bullinger, Lars; Stintzing, Sebastian; le Coutre, Philipp (Frontiers in Oncology, 2021)
Progress in oncological treatment has led to an improved long-term survival of young male cancer patients over the last decades. However, standard cancer treatments frequently implicate fertility-damaging potential. Cryopreservation of sperm is the current standard option to preserve patient’s fertility after treatment, yet long-term data on usage and reproductive experiences is still limited. Natural fertility after treatment and especially in relation to the type of treatment has been poorly analyzed so far. Therefore, we performed a retrospective survey including male patients with an indication for gonadotoxic treatment who cryopreserved reproductive material at our institution between 1994 and 2017. Study questionnaires regarding treatment, material usage, and reproductive outcomes were sent to eligible patients. Additionally, semen analyses of study participants from the time of cryopreservation were evaluated. A total of 99 patients were included in the study. Respondents’ median age was 38.0 years. Most frequent diagnoses were testicular cancer (29.3%) and lymphoma (26.3%). A further 8.1% suffered from autoimmune diseases. Testicular cancer patients had a significantly lower pre-treatment median sperm concentration (18.0 million/ml) compared to non-testicular cancer patients (54.2 million/ml). Until November 2020, the determined sperm usage and cumulative live-birth rate per couple were 17.2% and 58.8%, respectively. Most sperm users received treatments with high (40.0%) or intermediate (33.3%) gonadotoxic potential. 20.7% of all patients reported to had fathered at least one naturally conceived child after treatment, this being the case especially if they had been treated with less or potentially gonadotoxic therapies. In conclusion, our findings emphasize the importance of sperm cryopreservation in the context of male fertility preservation. Furthermore, they indicate that the gonadotoxic potential of patients’ treatments could represent a predictive factor for sperm usage.